Perancangan Sistem Informasi Penjualan dan Persediaan pada PT Selatan Jaya Prima Perkasa - Surja, Stephanie; Wongso, Rini (Bina Nusantara University, 2013)
This study aims to analyze the organization needs in sales and stock company process that related with the current business process at PT Selatan Jaya Prima Perkasa. The result will be used for developing an integrated system that can be the solution for the company needs in running their sales and to control theirinventory stock status as the main business of the company. The analyzed result in the company needs will be documented using unified modeling language. This information system is expected to simplify ease the company’s activitis in sales process and inventory stock control. This system will also minimize the data lost and human error usually caused by manual process of transactional data storage.